On the Way to in vitro Platelet Production - Strassel, Catherine; Gachet, Christian; Lanza, François (Frontiers in Medicine, 2018)
The severely decreased platelet counts (<10-30.103 platelets/µL) frequently observed in patients undergoing chemotherapy, radiation treatment or organ transplantation are associated with life-threatening increased bleeding risks. To circumvent these risks, platelet transfusion remains the treatment of choice, despite some limitations which include a limited shelf-life, storage-related deterioration, the development of alloantibodies in recipients and the transmission of infectious diseases. A sustained demand has evolved in recent years for controlled blood products, free of infectious, inflammatory and immune risks. As a consequence, the challenge for blood centers in the near future will be to ensure an adequate supply of blood platelets, which calls for a reassessment of our transfusion models. To meet this challenge, many laboratories are now turning their research efforts towards the in vitro and customized production of blood platelets. In this review we provide an overview of the arguments in support of research focusing on the culture of platelets for transfusion purposes and recapitulate the main advances in this quickly evolving field, while noting technical limitations which still need to be overcome.